Community participations and health care in rural areas – the differences between Swedish and Indonesian system - Jenny Samuelsson (Berita Kedokteran Masyarakat (BKM), 2018)
The Swedish and Indonesian health care systems are both decentralised, and every day health care is based on activities performed in district hospitals and primary health care centres. The main difference between the Swedish and Indonesian health system is the existence of posyandus, not found in Sweden. Meanwhile the Swedish system only allows health professionals, the Indonesian posyandus are run voluntarily by health cadres and are more based on community participation. However, as the major health problem faced by the Swedish health care is an overloaded system and a growing number of elderlies, an approach developed in rural parts of northern Sweden are the virtual health rooms. The virtual health room, a self-serviced room for basic health monitoring, is based on community participation, and may be called the Swedish version of posyandu. Future models for increased community participation in Sweden are thought to be further developed through such virtual health rooms, and with the movement from country side to the Swedish cities.  Although the differences of the health systems in the two countries are many, we also share one very important similarity: the lack of health care professionals.